Peradaban Masyarakat Arab Pra Islam - Azmar Hidayat; Haidar Putra Daulay; Zaini Dahlan (Al-Ulum: Jurnal Pendidikan Islam, 2021)
This paper examines the civilization of pre-Islamic Arab society, which can be said to be a fairly dark civilization. How could the events that happened there were really sad, such as: idols who are powerless to worship, a cruel government that doesn't pay attention to its people, women like there is no value, married at will without any restrictions on polygamy, just as anyone can gather, and etc. For more details, this paper will explain in more detail. Keywords: Civilization, Arab Society, Pre-Islam